Desafios no ensino e na aprendizagem da neurologia durante a formação médica em um curso com currículo em espiral estudo qualitativo com professores e alunos de uma escola de medicina - Tavares, Fabíola Cristina Santos (2023)
Neurological diseases have increased worldwide, mainly due to demographic and epidemiological transitions. In this sense, studies point to difficulties expressed by medical students and general practitioners with regard to the care of patients with such morbidities, with neurology being considered the most complex specialty and with the greatest gaps throughout academic training. It is also verified that there are few studies that portray the reasons behind such a problem. These factors can compromise the physician's basic education, especially with regard to the application of this field of knowledge in professional practice. Given the above, the main objective of this study is to know the perception of students and professors about the teaching and learning of contents and practices in the field of neurology in different periods of a medical course. This is an exploratory research with a qualitative methodological approach that will be carried out with professors and students of the Medicine course at the Universidade Federal de São João Del Rey (UFSJ), campus Centro-Oeste (UFSJ-CCO), located in the city of Divinópolis, Minas Gerais. Because it is a qualitative study, the final sample size was not fixed a priori, but (re)adapted throughout the field work. For these reasons, an intentional sample was chosen, with the final number of participants being determined by the criterion of empirical data saturation. Data were collected by conducting focus groups. The meetings took place in a remote format, via the Google Meet application, with a link restricted to participants who agreed to participate in the study. Data were analyzed using the content analysis technique. It was observed that the neurology approach is partially integrated with the neurosciences throughout the undergraduate curriculum. However, there is a lack of practical applicability parallel to the theoretical content taught. In addition, in line with the current literature, the subject is considered more difficult than the other specialties. All this culminates in insecurity and resistance in dealing with patients with neurological complaints. It is hoped that the results obtained in this study may encourage the development of other related research and contribute to the proposition of educational strategies for teaching and learning neurology throughout medical training.